The training situation and its impact on some indicators of the body To get rid of the excess heat of the players of the national team The national handball Experimental research (Journal of the College of Basic Education, 2022)
The continuation of the training process leads to the occurrence of some physiological responses.Positivity as a result of the body's tremendous ability to respond to the regular training stimuli, which increasesThe ability of the individual athlete to bear the requirements of training, and thus ensures the continuity of upgrading the level